Odpowiedzi

2010-03-15T20:58:56+01:00
Jedna trzecia x - 2 = x + 2
-2/3x=4
x=-6

1 - sześć siódmych x = cztery siódme
-6/7x=4/7-1
-6/7x=-3/7
x=1/2

6( jedna czwarta x - 2 ) = 18
6/4x-12=18
3/2x=30
x=20
3 3 3
2010-03-15T21:00:40+01:00
1/3*x - 2 = x + 2 |/2
x - 6 =3x + 6
-12 = 2x |/2
x= -6

1- 6/7*x = 4/7
7 - 6x = 4
-6x = -3 |/ (-6)
x = 3/6
x= 1/2

6( 1/4*x - 2) = 18 |/6
1/4*x - 2 = 3 |/4
x-8 = 12
x=20
1 5 1
2010-03-15T21:01:07+01:00
A. 1/3x-2=x+2
1/3x-x=2+2
-2/3x=4/:(-2/3)
x=1/4*(-2/3)
x=--2/12=-1/6
b.1-6/7x=4/7
-6/7x=4/7-1
-6/7x=-3/7/:(-6/7)
x=-3/7*(-7/6)
x=1/2
c.6(1/4x-2)=18
6*1/4x-12=18
6/4x=12+18
6/4x=30/:6/4
x=20